Overlooking Issues and Prospective Resolutions Behind the Prosperity of Three-Dimensional Porous Carbon Supercapacitor Electrodes - Liu, Tianyu (Frontiers in Energy Research, 2020)
The past decade has witnessed the boom of porous carbon materials, especially three-dimensional (3D) ones, as supercapacitor electrode materials. Their large surface areas, tunable pore volumes, adjustable degrees of pore interconnectivity, and the potential to possess hierarchical porous networks have enabled them to achieve simultaneously high capacitance and excellent rate capability. This feature is challenging for non-3D counterparts but favorable for supercapacitors. However, behind the prosperity come the problems, and unfortunately, most of the issues are left unacknowledged and unaddressed in the literature available. This perspective aims to identify these problems, discuss the reasons for overlooking, and provide possible solutions to address these issues. The author wishes this article will draw the attention of researchers in electrochemical energy storage to tackle these roadblocks in the future development of 3D porous carbon electrodes in supercapacitors.